PERAN PEREMPUAN DI BERBAGAI SEKTOR KEHIDUPAN - Alfia Apriani; Ratnawaty Ratnawaty (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
This writing highlights the functions and the roles of woman in some aspects of life, like in faiths, worships, education, social and political struggle in society. Anticipating the challlenge of this era, the woman should function both in domestic and in public roles in order to keep and balancing their own and respective existence. The movement and the progress of woman should be supported by creating chances and eliminating the hindrance-factors like unwelcoming attitude toward their appearance outside the house affairs, and eliminating the so called ‘fear-factors’ around the woman. All these factors can be handled by improving their skills, innovative and creative works.